I-bin : the intelligent and entertaining bin - Noor, Nolok; Haq, Mohammad Wasiul (BRAC University, 2014)
This thesis report submitted in partial fulfillment of the requirement for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.